2017
DOI: 10.1186/s13068-017-0978-7
|View full text |Cite
|
Sign up to set email alerts
|

Renewable synthesis of n-butyraldehyde from glucose by engineered Escherichia coli

Abstract: Background n-Butyraldehyde is a high-production volume chemical produced exclusively from hydroformylation of propylene. It is a versatile chemical used in the synthesis of diverse C4–C8 alcohols, carboxylic acids, esters, and amines. Its high demand and broad applications make it an ideal chemical to be produced from biomass.ResultsAn Escherichia coli strain was engineered to produce n-butyraldehyde directly from glucose by expressing a modified Clostridium CoA-dependent n-butanol production pathway with mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Chemical feedstock BW25113 630 mg/L Expression of mono-functional aldehyde dehydrogenase instead of the conventional bi-functional aldehyde/alcohol dehydrogenase (Ku et al, 2017).…”
Section: Butyraldehydementioning
confidence: 99%
See 1 more Smart Citation
“…Chemical feedstock BW25113 630 mg/L Expression of mono-functional aldehyde dehydrogenase instead of the conventional bi-functional aldehyde/alcohol dehydrogenase (Ku et al, 2017).…”
Section: Butyraldehydementioning
confidence: 99%
“…Intermediates of the Clostridial pathway have also been produced. The synthesis of butyraldehyde was achieved through replacing the bifunctional alcohol aldehyde dehydrogenase in the butanol pathway with a mono-functional aldehyde dehydrogenase (Ku et al, 2017). Butyraldehyde serves as a precursor to biological propane production (Kallio et al, 2014).…”
Section: Biofuelsmentioning
confidence: 99%
“…Subsequently, butyryl‐CoA is converted to butyrate via butyryl‐phosphate. A synthetic chain elongation pathway extending acetyl‐CoA to butyryl‐CoA has been developed for efficient butanol (Bond‐Watts, Bellerose, & Chang, ; Shen et al, ) and butyraldehyde (Ku, Simanjuntak, & Lan, ) biosynthesis. However, we previously identified that thiolase, catalyzing the Claisen condensation of two acetyl‐CoA, is a major limiting step for cyanobacterial butanol production.…”
Section: Introductionmentioning
confidence: 99%
“…[114d, 186] An ethoxylated version of 6d (EO-6d)w as pre-pared by allowing the growth of short oligo(ethylene oxide) chains on each hydroxy group of 6d followed by capping with ECH and carbonation. [187] As the latter aldehydes can be derived from bio-alcohols or from the fermentation of glucose, [188] 6d and 6e can be regarded as potentially renewable carbonates. [184] Trimethylolpropane and pentaerythritol, used as reagents for the synthesis of 6d and 6e,respectively,can be prepared by the reactions of formaldehyde with n-butyraldehyde or acetaldehyde.…”
Section: Monomers With Multiple 5cc Moietiesmentioning
confidence: 99%
“…[184] Trimethylolpropane and pentaerythritol, used as reagents for the synthesis of 6d and 6e,respectively,can be prepared by the reactions of formaldehyde with n-butyraldehyde or acetaldehyde. [187] As the latter aldehydes can be derived from bio-alcohols or from the fermentation of glucose, [188] 6d and 6e can be regarded as potentially renewable carbonates. 6f can be prepared from glycerol and ECH.…”
Section: Monomers With Multiple 5cc Moietiesmentioning
confidence: 99%